An alternative explanation of back-relaxation in ionic polymer metal composites. (May 2017) - Porfiri, M.; Leronni, A.; Bardella, L.
Abstract: The phenomenon of back-relaxation in ionic polymer metal composites (IPMCs) has attracted the interest of the scientific community for two decades, but its physical origins largely remain elusive. Here, we propose an explanation of this phenomenon based on Maxwell stress. From first principles, we demonstrate that IPMC actuation is controlled by the nonlinear interplay between osmotic and electrostatic phenomena. While osmotic pressure tends to produce a rapid bending toward the anode, Maxwell stress generates a slow relaxation toward the cathode. The relative weight of these phenomena is determined by the applied voltage. At voltage levels comparable to the thermal voltage, IPMC actuation is dominated by osmotic effects. As the applied voltage is increased, Maxwell stress overcomes the osmotic pressure, leading to back-relaxation. Highlights: We theoretically investigate actuation of ionic polymer metal composites. Electric polarization, ion mixing, and mechanical stretching are modeled. Back-relaxation is explained without reversing the cations' motion. Cations' motion breaks the symmetry of the electric field at the electrodes. Maxwell stress could be the critical explaining variable for back-relaxation. Graphical abstract: